Escrit??rios de gerenciamento de projetos e orienta????o empreendedora: An??lise de sua rela????o em empresas de software - Belfort, Ana Claudia (2015)
Both the Project Management Office (PMOs) as the Entrepreneurial Orientation (EO) emerge in literature and business environment as themes that enable organizations most strategic direction, since both are present in corporate strategies. The implementation of PMOs can enhance the way the organization manages its projects. EO and its dimensions (innovativeness, risk taking, proactiveness, autonomy and competitive aggressiveness) can contribute positively to the organizations, outlining their strategies. Some authors claim a relationship between project management and EO; however, there is no evidence of studies that address the PMO and EO constructs together. In this context, this thesis aims to analyze the relationship between PMOs and EO software companies. In this sense, the question guiding this study is to research "as the project management office relates to the entrepreneurial orientation in software companies?". For purposes of answering it, it was necessary to revisit the literature on the constructs of this study (PMO and EO), developing a conceptual framework allowing to obtain information to identify the organization's project management system, characterize the existing PMO in the organization, identify the dimensions of the EO in the analyzed PMOs and analyze the EO in PMOs considering the Strategic PMS Model proposed by Cooke-Davis, Crawford and Lechler (2009). This research is considered applied, exploratory and qualitative. Through a multiple case study in four software companies, which had at least one PMO, hit up the proposed objectives. Therefore, data collection strategies used were semi-structured interviews with managers of the project offices, analysis of documents and records in files. As analysis strategies were adopted the intracasos and intercasos analysis. The results confirmed as true the proposition of this study which states that depend on the type of project management office adopted by the organization, the entrepreneurial orientation can manifest itself in different ways. The dimensions innovativeness, risk-taking and autonomy were identified in PMOs for companies B and C (PMCOE and PrgMO, respectively), while the size proactivity has also been identified in PMO companies A (PMO type PSO) and the competitive aggressiveness scale was partially identified only in PMO company B. As for the PMO company D (PMCOE), the innovativeness, risk-taking, proactivity and autonomy were partially identified. This study contributes to both the academy, especially in the studies of PMOs, EO and both set mode, as well as the organizational practice and project management, providing subsidies that allow managers to identify whether there are and how is the relationship between PMO and the EO in your business, and enables the strategic direction of the company by applying entrepreneurial practices in PMOs.in your business, and enables the strategic direction of the company by applying entrepreneurial practices in PMOs.